Speculative Attacks, Forward Market Intervention and the Classic Bear Squeeze - Lall, Subir (Washington, D.C. : International Monetary Fund, 1997)
A typical strategy used by speculators to launch an attack on a fixed exchange regime is the use of forward markets. Central banks also intervene in forward markets to counter speculation. This paper addresses the question of how an attack is launched on the forward market, and what the optimal policy response to such speculation is in the forward and spot markets. The paper also demonstrates how central banks can impose a bear squeeze on speculators. Recent events in South East Asian currency markets are interpreted within the framework of the model's predictions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet